WHITE SUPREMACY AND STRUCTURAL RACISM IN “THE SHAWSHANK REDEMPTION” BY FRANK DARABONT - Erni Rahmawati; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2020)
The purpose of this study was to analyze white supremacy and structural racism in the film "The Shawshank Redemption". The method used is descriptive-qualitative to describe white supremacy and structural racism in the film. Data is obtained, analyzed and explained based on dialogues contained in the film, namely: 1) white supremacy that is analyzed from a) the appearances of the character using a sequence table, and b) visible glorification and invisible glorification using glorification dialogue table, and 2) structural racism, using binary opposition, namely positive and negative characterization of the characters. By the sequence table, the character that is predominant in the film is Andy Dufresne. From the glorification dialogue table, visible glorification gets the highest presentation while invisible glorification gets the lowest presentation. This shows that white supremacy exists in American film. As for structural racism, the negative characterization of the supporting characters is the highest while the negative characterization of the main character is the lowest. This shows that structural racism exists in American film.Key Words: American film; drama; white supremacy; structural racism.